SISTEM INFORMASI LAYANAN JASA SAVE MY SHOE BERBASIS WEB MENGGUNAKAN METODE AGILE SCRUM - Syahfikri Sauqi Marpaung; Fachrul Rozi Lubis (P3M STMIK Profesional Makassar, 2025)
Save My Shoe is a shoe cleaning service business that faces challenges in managing transactions, recording customer data, and monitoring services due to the absence of an integrated information system and reliance on social media. This study aims to design and implement a web-based information system that supports operational processes and service delivery in a more efficient and structured manner. The system was developed using the Agile method with a Scrum approach, allowing each feature to be built incrementally and tailored to User needs. The system includes features such as registration, Login, service ordering, payment, service progress tracking, and transaction reporting, with User roles consisting of admin and customer. Based on testing using the Black Box Testing method, all system functionalities operated according to the defined requirements. This information system is expected to improve business management effectiveness, enhance service transparency, and support the sustainable digitalization of MSMEs.